Gaucher's disease – ocular manifestation and traetment - Filipek, Erita; Koraszewska-Matuszewska, Bronisława (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Gaucher’s disease is the most common lysosomal storage disorder due to a deficiency of glukocerebrosidase activity. It leads to an accumulation of glukosylceramide within the cells of the the reticuloendothelial system. Gaucher’s disease is divided into three subtypes based on clinical symptoms. Type I – nonneuronopathic – chronically progressive in adulthood, type II – acute neuronopathic – infantile form lead up to the difficult damage nervous system, and type III – juvenile form – subacute neuronopathic. The aim of this paper is to present the typical ocular symptoms which occured in the disease. Gaucher’s disease is the lysosomal storage disorder which is treated by enzyme replacement therapy.